ANALYSIS OF DIFFERENCES IN CORPORATE VALUES AND FINANCIAL PERFORMANCE THREE MANUFACTURING INDUSTRY SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE - Titi Purwantini; Endang Brotojoya (STIE AUB Surakarta, 2019)
The purpose of this study was to obtain empirical evidence of differences in corporate value and financial performance of the three manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study were 60 manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2017. Sampling techniques were purposive sampling. The division of sector 1 consists of cement companies, basic chemicals, porcelain and glass, metals, plastics and packaging, animal feed, wood and pulp, for sector 2 consists of machinery and heavy equipment companies, automotive and its components, textiles and garments, bedding feet and cable. Whereas for sector 3 consists of consumer goods, namely tobacco, cosmetics, pharmaceuticals and household appliances. Data analysis techniques consist of normality testing and different Paired Sample Test tests.Research results prove that based on Differential Test Paired Sample Test sectors 1 and 2. Manufacturing Companies listed on the Stock Exchange have significant differences in financial performance seen from the Current Ratio and Debt Equity Ratio while from Earning per Share, Net Profit Margin and Expencess On Sales there is no difference . Based on the Different Test Paired Sample Test is seen from the Earning Per Share ratio there is a significant difference in financial performance between Sector 1 and sector 3. Based on the Different Paired Sample Test seen from the Debt Equity Ratio, there are significant differences in financial performance between Sector 1 and sector 3 ... There are also significant differences in the financial performance of sectors 2 and 3 from the point of view of Earning Per Share. Based on the Different Paired Sample Test Test, there was no difference in company values in the three manufacturing companies listed on the Indonesia Stock Exchange.